Financial and social inclusion in Europe - Domenica Federico; Riccardo Grazioli; Maria Adele Milioli; Antonella Notte; Lucia Poletti (European Investment Fund (EIF), 2021)
This paper looks at the state of financial and social inclusion and financial sector development in EU Member States. More precisely, one of the objectives is to find out whether financial and social exclusion can coexist in the same countries, taking into account the development of the financial sector. The study outlines extensive literature on definitions and measures of financial and social inclusion. It also identifies clusters of countries, with internally similar but externally distinct characteristics. Methodologically, the research collects and analyses data extrapolated from different sources in the period 2016-2017. The methodology exploits a Principal Component Analysis (ACP) and a Cluster Analysis.
Keywords: 330; Finanzielle Inklusion; Soziale Integration; EU-Staaten